PERAN GURU DALAM MENGATASI KESULITAN BELAJAR MEMBACA PERMULAAN PADA SISWA SEKOLAH DASAR - Susilahati, Susilahati; Nurmalia, Laily; Ninda Fadhilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem of students' initial reading learning difficulties has an impact on learning outcomes and the smoothness of the teaching and learning process. For this reason, so that students are able to read and do not miss out on lessons and are able to understand the material presented by the teacher, teachers must play a role and make every effort to overcome students who have difficulty reading so that students do not experience delays in receiving learning in class. The aim of this research is to analyze the role of teachers in overcoming difficulties in learning to read at the beginning of elementary school students. The method used is descriptive qualitative with data collection through observation, interviews and documentation. Based on the research results obtained, teachers at SDIT Roudhotul Jannah Kota Bekasi have carried out their roles as best as possible by providing structured teaching, using multisensory learning methods, providing direct feedback, intervening early, creating a positive learning environment and involving parents.